Enhanced sludge dewatering and drying comparison of two linear polyelectrolytes co-conditioning with polyaluminum chloride. Issue 58 (13th December 2016) - Pambou, Y.B.; Fraikin, L.; Salmon, T.; Crine, M.; Léonard, A.
Abstract : This paper investigated the influence of polyaluminum chloride (PAX-14) co-conditioning with two linear polyelectrolytes on the dewatering and drying performances of urban residual sludge. Experiments were carried out on activated sludge samples collected after thickening from the Grosses Battes wastewater treatment plant. Dual conditioning implying PAX-14 coagulant and two cationic polymers, only differing by their molecular weight, were tested. The first part of the study was an experimental study of sludge dewatering improvement in terms of dry solids content of the dewatered cake and the evaluation of specific resistance to filtration (SRF) determined using a filtration–compression cell. The results showed that dual conditioning including PAX-14 addition has a positive impact on the dewatering process, based on the increase of cake dryness limit after PAX-14 addition. It was also found that the use of filtration theory based on Carman's equation to determine the SRF parameter presents some limitations to describe accurately the filtration step. The second part of the work consisted in drying the sludge cake obtained after the dewatering stage. The results indicated that, for the same water content, the use of both substances: PAX-14 and flocculant helped to achieve higher drying rates in comparison with the use of a single conditioning to flocculate the bio-material, allowing a reduction of the drying time. Based on the statistical analysis results, the efficiency of the two conditioning types were shown to be the same. The shrinkage response exhibited a linear decrease with two zones. For both sludge conditioned, the final volume reduction was found to be closed to 70% after drying and was directly dependent on the nature of the sludge.